2010
DOI: 10.12693/aphyspola.117.493
|View full text |Cite
|
Sign up to set email alerts
|

Frequency Dependent Electrical Characteristics οf Au/n-Si/CuPc/Au Heterojunction

Abstract: Electrical characteristics of the heterojunction fabricated by thermal deposition of copper phthalocyanine (CuPc) on an n-silicon substrate have been investigated. The frequency has significant effect on capacitance (C), conductance (G) and series resistance (R s ) interface states (D it ) of the junction. Measured capacitance and conductance were corrected for R s . The conductance technique was used to measure the density of the interface states. This method revealed the value of the interface state density … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
9
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 24 publications
0
9
0
Order By: Relevance
“…Increasing the alternating-voltage frequency from 700 up to 5000 Hz, the capacitance tends to reach a saturated value, while a linear reduction exists for the resistance. It is suggested that at a high frequency (i.e., more than 3000 Hz), the interface states along the Schottky junction cannot follow and their contribution to the capacitance turns trivial …”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Increasing the alternating-voltage frequency from 700 up to 5000 Hz, the capacitance tends to reach a saturated value, while a linear reduction exists for the resistance. It is suggested that at a high frequency (i.e., more than 3000 Hz), the interface states along the Schottky junction cannot follow and their contribution to the capacitance turns trivial …”
Section: Resultsmentioning
confidence: 99%
“…It is suggested that at a high frequency (i.e., more than 3000 Hz), the interface states along the Schottky junction cannot follow and their contribution to the capacitance turns trivial. 26 To eliminate the interferences from the interface states, this work applies the 4500 Hz frequency of alternating voltage as the excitation for collecting reactance signals (X = −1/(2πf C); f: frequency of the alternating voltage). Figure S5 presents the photography of the Bi 2 O 2 Se sensor that is of two interdigitated electrodes, and the conductance channel of exposure is Bi 2 O 2 Se.…”
mentioning
confidence: 99%
“…The R s and N ss values are vital parameters for the electrical characteristics of the heterojunctions. The Nicollian-Brews method is appropriate to compute the R s value and expressed as [27][28][29]:…”
Section: Resultsmentioning
confidence: 99%
“…The Hill-Coleman method was employed to compute the N ss value. According to this method, the value of N ss was computed from the measured C-V-f and G-V-f curves by utilizing the following relationship [28,29]:…”
Section: Resultsmentioning
confidence: 99%
“…It appears that at higher frequencies, the interface states cannot follow the AC signal 28 and consequently cannot contribute much to the capacitance. This indicates that the interface states are responsible for the observed frequency variation in C p .…”
Section: Fesem Imagesmentioning
confidence: 99%